Counter-regulatory RAS peptides: new therapy targets for inflammation and fibrotic diseases? - Ávila-Martínez, Diana V.; Mixtega-Ruiz, Wendy K.; Hurtado-Capetillo, José M.; Lopez-Franco, Oscar; Flores-Muñoz, Mónica (Frontiers in Pharmacology, 2024)
The renin angiotensin system (RAS) is an important cascade of enzymes and peptides that regulates blood pressure, volume, and electrolytes. Within this complex system of reactions, its counterregulatory axis has attracted attention, which has been associated with the pathophysiology of inflammatory and fibrotic diseases. This review article analyzes the impact of different components of the counter-regulatory axis of the RAS on different pathologies. Of these peptides, Angiotensin-(1-7), angiotensin-(1-9) and alamandine have been evaluated in a wide variety of in vitro and in vivo studies, where not only they counteract the actions of the classical axis, but also exhibit independent antiinflammatory and fibrotic actions when binding to specific receptors, mainly in heart, kidney, and lung.Other functional peptides are also addressed, which despite no reports associated with inflammation and fibrosis to date were found, they could represent a potential target of study. Furthermore, the association of agonists of the counter-regulatory axis is analyzed, highlighting their contribution to the modulation of the inflammatory response counteracting the development of fibrotic events. This article shows an overview of the importance of the RAS in the resolution of inflammatory and fibrotic diseases, offering an understanding of the individual components as potential treatments.